Therapeutic environment design elements in Malaysia's medical tourism accommodations: an observation study - Faraj, Mohamad; Siow, May Ling; Maruthaveeran, Sreetheran (International Information and Engineering Technology Association, 2024)
This study evaluates the design elements for healthcare environments that prioritize patients' physical and psychological well-being in the Malaysian healthcare system, specifically focusing on medical tourism accommodations. In Malaysia, private hospitals often lack onsite accommodations and instead collaborate with nearby hotels. This research examines four hotels frequently recommended by multiple hospitals, using a qualitative observational method to observe and gather meaningful insights systematically. The study reveals that while existing designs have positively impacted the medical tourism industry, there is room for improvement. Interior environment design, encompassing elements such as lighting, ventilation, color schemes, noise management, furniture selection, and room layouts, is pivotal in promoting patients' health and recovery. Furthermore, incorporating natural elements such as landscapes, vegetation, and water features proves effective in enhancing the overall patient experience and reducing stress. The study emphasizes the importance of considering the surrounding environment, particularly in urban areas, where tourism benefits should align with medical tourists' health and recovery needs. In conclusion, this research contributes a conceptual framework for developing guidelines to design accommodations with therapeutic qualities. These guidelines can potentially enhance the well-being of medical tourists and further strengthen the growth of the medical tourism sector in Malaysia. © 2024 The authors.